2016
DOI: 10.1007/s00580-016-2274-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and morphological changes in rats exposed to platinum nanoparticles

Abstract: This study evaluated the toxicity potential of platinum (Pt) nanoparticles in Wistar rats. Wistar rats weighing between 180 and 193 g were randomly assigned into four groups. Animals in group 1 served as the control and received distilled water. Those in groups 2, 3, and 4 were administered with 10, 50, and 100 mg/kg body weight of Pt nanoparticles, respectively. At the end of treatments, the rats were fasted for 24 h and sacrificed under mild anesthesia. The blood and vital organs were collected and used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(18 reference statements)
3
15
0
Order By: Relevance
“…The nanoparticles were prepared as previously reported; AuNP, AgNP and PtNP were synthesized from HAuCl 4 , AgNO 3 and H 2 PtCl 6 , respectively, and stabilized with tannic acid/ ethanol [23,24,26,27]. Alloys of the nanoparticles (Ag-Au-Pt-NP, Ag-Pt-NP, Au-Pt-NP and Ag-Au-NP) were synthesized as previously reported [27] with little modification.…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles were prepared as previously reported; AuNP, AgNP and PtNP were synthesized from HAuCl 4 , AgNO 3 and H 2 PtCl 6 , respectively, and stabilized with tannic acid/ ethanol [23,24,26,27]. Alloys of the nanoparticles (Ag-Au-Pt-NP, Ag-Pt-NP, Au-Pt-NP and Ag-Au-NP) were synthesized as previously reported [27] with little modification.…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
“…The tryptophan-nanoparticle conjugates (AuNP TRP and AgNP TRP ) were prepared as previously described and characterized [28]. The resulting coloured solutions (AgNP, pale yellow; AuNP, ruby red; PtNP, dark brown; Ag-Au-Pt,-NP, dark-brown; Ag-Pt-NP, dark brown; Au-Pt-NP, dark wine red; Ag-Au-NP, brownish wine red; AuNP TRP , wine-red; and AgNP TRP , pale yellow) were filtered through 0.22-lm filters and characterized by use of UV/Vis spectrophotometry, inductively coupled plasma optical emission spectrometry (ICP-OES), energy dispersive X-ray spectroscopy (EDX) and transmission electron microscopy (TEM) [23,24,26,27,29].…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
“…Interesting is the fact that the activities of alkaline phosphatase and aspartate transaminase were reduced while the level of alanine aminotranferase was raised in the liver (both in tissues and serum). This study demonstrated that platinum nanoparticles caused morphological lesions, including inflammation (an increase in the total protein concentration in the heart, kidney and liver) and cellular degeneration [22].…”
Section: Oral Administrationmentioning
confidence: 71%
“…Adeyemi et al exposed Wistar rats to PtNPs via the oral route [22]. The animals received a daily dose of the studied nanoparticles (10, 50 or 100 mg/kg) for 30 consecutive days.…”
Section: Oral Administrationmentioning
confidence: 99%
“…A decrease in the level of serum urea after 56 days of administration of CcAgNPs observed in our study might be attributable to reduced amino acid degradation by the liver; moreover, this finding correlates with a decline in ALB levels in CcAgNPs-treated groups. Previously, studies showed that serum creatinine levels in animal model were significantly reduced suggesting enhanced glomerular clearance or impaired muscle metabolism [31,32].…”
Section: Discussionmentioning
confidence: 99%